PRÁCTICAS INCLUSIVAS Y SU INCIDENCIA EN LOS ESTUDIANTES CON NEE DE LA ESCUELA EDUCACIÓN BÁSICA EN LA ESCUELA "CIUDAD DE VINCES" DURANTE EL PERÍODO 2024-2025. - SANTILLÁN PEÑAFIEL.ADAMARI JAIRI (2024)
The following thesis deals with inclusive practices and their impact on students with SEN in the Basic Education school at the "Ciudad de Vinces" School during the period 2024-2025. The main objective of which is to determine inclusive practices and their impact on students with SEN in the Basic Education school at the "Ciudad de Vinces" School during the period 2024-2025. In which a research methodology with a mixed approach has been used, of an explanatory type trying to notice the effect on the research variables, with a descriptive - non-experimental design where investigative works were reviewed to collect information for said topic, aimed at a population of 170 students from the Ciudad de Vinces school located in the province of Los Ríos, Vinces canton. With a sample of 38 students, the technique used to collect data is the survey and the instrument used in this research was the questionnaire. Once the data was collected, they were tabulated, we selected the Excel statistical tool, obtained with instruments previously subjected to reliability and validity tests. The results have been analyzed statistically and showed a percentage of 71% consider that inclusive practices are necessary to strengthen their skills. Obtaining the conclusion that educational inclusion positively influences students with special educational needs, which adapts and responds to educational priorities.